A wireless flipper robot using interface free controller. - Jaafar, Haslina; Che Soh, Azura; Wan Hasan, Wan Zuha; Marhaban, Mohammad Hamiruce; Abd Rashid, Shaufiq (2013)
Robots have been developed by human to do various things to make our life easier. There are many approaches, systems and technologies can be applied to develop different types of robots depended on the usage. This paper presents the new approach of interfacing a wireless robot using IFC (Interface Free Controller). This controller offers a new concept of microcontroller embedded system developed for robotic application. IFC is an interfacing hardware and it configures the peripherals. This flipper robot is a fighting robot which previously participated in the robot war game. The complete design, interfacing, robot constructions, specification of the robot and testing processes are detailed out.